Calculation of the Average Electron Energy and Drift Velocity at Low Fields for Compound Semiconductor Gallium Arsenide (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The drift velocity and average energy of electrons in the central valley 〈OOO〉 G were calculated in compound semiconductor GaAs at low electric fields of about 4 kV/cm at room temperature. The drift velocity change at low temperatures was also studied in the low fields. The Boltzmann equation was solved using an analytical method based on the extension of the Legendre polynomial and a numerical method based on the finite difference method to obtain the unbalanced distribution function, and then solve it by preparing an algorithm using MATLAB.The obtained results were in agreement with the experimental results.